Implementation of Sustainable Tourism Development of Tourism Villages in Langkat Regency - Edy Sahputra Sitepu; John Sihar Manurung; Rismawati (International Journal of Applied Sciences in Tourism and Events, 2021)
This research is applied research, which seeks to encourage research to develop and manage destinations with the concept of sustainable tourism development (STD). STD is a concept that integrates the four pillars of tourism destination governance. This concept has been stated in the Regulation of the Minister of Tourism of the Republic of Indonesia Number 14 of 2016. The STD concept consists of four variables, among others; a) the implementation of effective management that is integrated and sustainable, b) strengthening the impact and economic benefits for local communities, c) strengthening and preserving socio-cultural, and d) paying attention to environmental sustainability around tourist destinations. This research aims to apply the STD concept for the development of tourism village potential. Specifically, this research is intended to encourage tourism village potentials in Sei Bingai and Tanjung Pura Districts, Langkat Regency, North Sumatra Province. So that in the end, it is hoped that Langkat Regency can have a well-managed tourist village based on the STD concept. The results showed that, based on the results of Confirmatory Factor Analysis (CFA) using AMOS 22 software, it was found that the existing variables were indeed relevant for analyzing the application of sustainable tourism development. Furthermore, based on the scoring carried out in the Focus Group Discussion (FGD) activities with key stakeholders, a ranking is carried out. Of the four existing aspects, the environmental aspect is in the good category (based on the excellent, good, average, and poor categories), while the sustainable integrated management variable, the variable economic benefits for the surrounding community, and the environmental conservation variable are in the good category. The results of the FGD also concluded that the majority of key stakeholders agreed that in Rumah Galuh Village and Pematang Serai Village, Langkat Regency would continue to be developed into a tourist village with a sustainable tourism development model.